Presentations of tetramethylammonium hydroxide dermal exposure and the valuable potential of diphoterine solution in decontamination: a retrospective observational study - Chih-Kang Huang; Alan H. Hall; Ming-Ling Wu; Chen-Chang Yang; Dong-Zong Hung; Yan-Chiao Mao; Jou-Fang Deng (BMC, 2020)
Abstract Background Tetramethylammonium hydroxide (TMAH) is a quaternary ammonium compound that is both a base corrosive and a cholinergic agonist, and it is widely used in the photoelectric and semiconductor industries. It causes corrosive skin injuries and systemic cholinergic toxicity with death primarily resulting from respiratory failure without efficacious early decontamination. Methods A retrospective observational study was performed of all cases of TMAH exposure reported to the Taiwan Poison Control Center between July 2010 and October 2017. Retrieved medical records were independently reviewed by two trained clinical toxicologists. Results Despite immediate (< 5 min) skin decontamination with copious amounts of tap water, one patient exposed to 25% TMAH involving ≥5% of total body surface area (TBSA) developed significant systemic toxicity. Patients exposed to 25% TMAH involving ≤1% TBSA developed first-degree chemical skin injuries but no systemic toxicity. Among patients exposed to lower concentrations (≤2.38%) of TMAH, the majority only experienced first-degree chemical skin injuries without systemic signs. Patients exposed to 0.5% TMAH involving nearly their entire TBSA developed no chemical skin injuries or systemic toxicity. All patients who had only first-degree chemical skin injuries did not develop systemic toxicity after exposure to either 2.38% or 25% TMAH. Conclusions TMAH acts as an alkaline corrosive and cholinergic agonist. Systemic signs attributable to TMA+ can rapidly lead to respiratory failure and death after dermal exposure. We have demonstrated that an amphoteric solution may be efficacious for skin decontamination on-site immediately to prevent or ameliorate such toxicity. This practice especially carries a valuable potential in managing victims (patients) who have been exposed to those chemicals with immediate life-threatening toxicity (e.g. TMAH), suggesting that its early utilization deserves further study.